Focal nodular hyperplasia of the liver Diagnostic and therapeutic aspects - Rodríguez, Gustavo; Estefan, Alberto; Montano, Daniel; Almeida, Edgardo (Cirugía del Uruguay, 1996)
Focal nodular hyperp/asía (FNH) is an ínfrequent benígn tumor of the liver whích general/y affects young woman. lt is asymptomatíc in most cases or a findíng duríng laparotomy performed far a dífferent cause. The aím of thís paper is to present a case of focal nodular hyperplasía wíth unusua/ clínica/ features. The authors poínt out the díffículty in estab/íshíng pre-operatíve diagnosis wíth certaínty Final/y they make a revísíon of therapeutíca/ conduct far these tumors